Rapid co-creative assessment for actionable circular food systems - Elisabeth Obeng; Sabine Desczka; Bobby Tsvetkov; Inder Kumar; Sophie Galema (Journal of Agriculture, Food Systems, and Community Development)
This paper focuses on the use of rapid assessments for local food systems in eight African cities (Bamenda, Cameroon; Franceville, Gabon; Ibadan, Nigeria; Lagos, Nigeria; Moyamba, Sierra Leone; Nairobi and Nakuru, Kenya; and Tamale, Ghana). The INCiTiS-FOOD project (INtegrated and Circular Technologies for Sustainable city region FOOD systems in Africa) conducted a food systems assessment using a bottom-up and living lab approach to gain insights into the local potential for circular technologies centered around aquaponics, hydroponics, and insect farming. The findings allowed us to define a strategic direction and highlights the need for more fish and locally grown indigenous vegetables, as access to these disciplines has been limited by a lack of knowledge facilities and finances. We learned that co-creative rapid assessments are a promising method to raise awareness of the specific opportunities, challenges, and bottlenecks in the community, and to align the local community with actionable food system transformation.